2019
DOI: 10.1002/cam4.2008
|View full text |Cite
|
Sign up to set email alerts
|

The average relative dose intensity of R‐CHOP is an independent factor determining favorable overall survival in diffuse large B‐cell lymphoma patients

Abstract: The prognosis of diffuse large B‐cell lymphoma (DLBCL) patients depends on lymphoma‐ and patient‐related risk factors and is best estimated by the international prognostic index (IPI). The aim of the study was to determine whether the average relative dose intensity (ARDI) of an anthracycline‐containing regimen could predict DLBCL outcome independently from the IPI. We analyzed 223 white Caucasian DLBCL patients who completed at least four cycles of first‐line immunochemotherapy with rituximab, doxorubicin, cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 28 publications
(27 reference statements)
3
15
1
Order By: Relevance
“…Early studies in NHL patients treated with an anthracycline-containing induction regimen showed that 28% of patients had an RDI <70%, which was associated with a decreased response rate and shorter overall 2-year survival [5]. Similar findings have been reported in more recent studies with the rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) regimen, noting poor survival associated with RDI of less than 50-90% (Table 1) [47][48][49][50].…”
Section: Article Highlightssupporting
confidence: 63%
“…Early studies in NHL patients treated with an anthracycline-containing induction regimen showed that 28% of patients had an RDI <70%, which was associated with a decreased response rate and shorter overall 2-year survival [5]. Similar findings have been reported in more recent studies with the rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) regimen, noting poor survival associated with RDI of less than 50-90% (Table 1) [47][48][49][50].…”
Section: Article Highlightssupporting
confidence: 63%
“…The DI of chemotherapy affects the prognosis of malignant diseases, and in DLBCL, a reduced ARDI of R‐CHOP was associated with poor prognosis 11‐15 . A relatively high median ARDI of CHOP for the treatment of DLBCL has been observed in clinical practice 14,21 ; in a nationwide study from the United States, for example, the median ARDI was 83%, and the DI was less than 45% in only 5% of patients 22 . In contrast, the median ARDI in aggressive ATL patients who received intensive chemotherapies was only 60% in our study.…”
Section: Discussionmentioning
confidence: 99%
“…10 The DI of chemotherapy affects the prognosis of malignant diseases, and in DLBCL, a reduced ARDI of R-CHOP was associated with poor prognosis. [11][12][13][14][15] A relatively high median ARDI of CHOP for the treatment of DLBCL has been observed in clinical practice 14,21 ;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average relative dose intensity of the entire treatment was 91%, which was above the recently recommended 90% in lymphoma therapy. 24 Overall, 35 of the 188 patients (19%) required at least one dose reduction during treatment with escBEACOPP; in 29 cases, bleomycin and vincristine infusion was omitted on the eighth day of treatment because of neutropenia. In ABVD regimen, no We did not formally assess fertility, but it should be noted that 48 pregnancies have been reported after completion of therapy (28 women and the wives of 20 male patients).…”
Section: Resultsmentioning
confidence: 99%